Multiple systemic diseases complicated by bisphosphonate osteonecrosis: a case report - Carini, Fabrizio (CIC Edizioni Internationali, 2012)
AIMS: this work aims at demonstrating that multiple systemic conditions, in association with the development of bisphosphonate associated osteonecrosis of the jaw (ONJ), increase the risk of complications and may lead to hospitalization. For this reason the dental approach to patients with multisystem disease should be carefully managed by a team of specialists. CASE REPORT: a case of mandibular necrosis associated with intake of oral bisphosphonates in a complex systemic context is described. RESULTS AND DISCUSSION: many different diseases and systemic conditions may draw the line at oral surgery. Multiple treatments (e.g. antithrombotic, calcium channel blockers, diuretics, antibiotics and bisphosphonates) can alter the normal physiological response to tissue healing. CONCLUSIONS: patients taking bisphosphonates for more than three years (i.e. the term over which the risk of ONJ increases according to the literature, in presence of complex systemic situations, need to be carefully managed during the pre-operative, peri-operative and postoperative phases through a synergistic collaboration among different kind of specialists.